Pengaruh Pupuk Organik Limbah Kelapa Sawit dan Pupuk Anorganik terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) pada Pembibitan Utama - Hidayat, Kgs Agus Taufik; Saleh, Busri; Hermansyah, Hermansyah (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2017)
Palm oil mill waste is one of the biggest problems in palm oil mill development, hence the need for technology to treat the waste in order to be utilized. This study aims to obtain the composition of organic fertilizer solid waste palm oil factory combined with inorganic fertilizer in the main seedling of oil palm, carried out in the nursery garden of PT. Bio Nusantara Teknologi, Kec. Pondok Kelapa, Central Bengkulu District, from January 2016 to April 2016 with a height of 13 meters above sea level, using Completely Randomized Design (RCD), a factor with 4 replications. Dosage of combination Organic Fertilizer (POP) and Inorganic Fertilizer consisting of 6 levels, namely: O0 = 100% Inorganic (50 g / polybag) + 0% Organic (0 g / polybag), O1 = 80% Inorganic (40 g / polybag) + 20% Organic (100 g / polybag), O2 = 60% Inorganic (30 g / polybag) + 40% Organic (200 g / polybag), O3 = 40% Inorganic (20 g / polybag) + 60% Organic (300 g / polybag), O4 = 20% Inorganic (10 g / polybag) + 80% Organic (400 g / polybag), O5 = 0% Inorganic (0 g / polybag) + 100% Organic (500 g / polybag) ). The results showed that the combination of fertilizer treatment was significantly different from the variability of green leaves, the increase of seedlings 12 weeks after planting (MST), stem diameter 12 MST and leaf-breaking time, and not significantly different on the leaves leaf variable 12 MST.Keywords: palm oil waste, solid organic fertilizer, inorganic fertilizer, palm oil nursery